Heavy metal content in mangrove sediment of Sungai Sepetang and Sungai Tiram Laut In Matang Mangroves Forest, Perak, Malaysia - Hamzah, Ahmad Hanafi (2019)
Woody plants that capable to grow in extreme conditions such as in anaerobic muddy soil, high salinity, rough winds, hot and humid weather are commonly called mangrove plants. These mangrove creatures usually can be found in tropical and subtropical area; between land and sea.Elevated concentration of heavy metals in sediment have detrimental consequences on enviromental.This study was conducted to response to environmental problems of Malaysia. Thus, the objectives of this study were: (1) to detemine status of heavy metals contents in sediment at Sungai Sepetang and Sungai Tiram laut, Perak; (2) the specific objective to assess and compare of heavy metal contents in sediment at Sungai Sepetang and Sungai Tiram laut; (3) Comparison of the data analysis according to different national and international standards. For this research, the samples were collected during the wet season. A total of 150 sediment samples were collected with different depth (of 0-15 cm, 15-30 cm, 30-50 cm, 50-100 cm, and >100 cm) from upstream, middle stream, and downstream of river at each study area.To determination and level of five heavy metals (Zn, Fe, Cd, Pb, and Cu) from Sungai Sepetang and Sungai Tiram laut, and for the portion of sediment which passing through the 2mm sieve were determined the study.The metal contamination in sediment are also evaluated by applying Geo-accumulation Index (I-geo). The results showed that the sediment at Sungai Sepetang was sandy loam clay at all depths and the sediment at Sungai Tiram Laut was sandy loam. The sediment pH of this area was acidic, where the soil at the deepest level showed a low pH. As for electrical conductivity (EC) at Sungai Sepetang and Sungai Tiram Laut, the range was from 17.239 to 17.871 dS/m. Furthermore, both rivers showed concentration of the heavy metals Cu, Pb, and Fe; however, Cd and Zn were not detected. The results also revealed that Sungai Sepetang had a higher concentration of heavy metal than Sungai Sepetang , Where the contamination of sediment was higher (Fe) in zones and depth. Based on result , the comparison the concentration of heavy metal in sediment with different zones and depth at Sungai Sepetang and Sungai Tiram Laut was found that Copper (Cu), Lead (Pb),and Iron (Fe) are not dangerous in sediment from other studies .I-geo index demonstrated that most of the embraced metal have index value below zero.This shows the river sediment is unpolluted.The present study on heavy metal concentration in the sediment of Sungai Sepetang and Sungai Tiram Laut, Matang Mangrove Forest Reserve, will be useful for rational planning of contamination control strategies and their prioritization.